The Effect of Environmental, Social, and Governance Performance on Firm Value with Proper Rating as A Moderating Variable - Yulius Jogi Christiawan; Ghea Ariaristy Junio; Regita Manurung (Accounting Department, School of Business and Management - Universitas Kristen Petra, 2026)
Using the PROPER rating as a moderating variable, this research examines the effects of environmental, social, and governance (ESG) performance on firm value using panel data from non-financial corporations listed on the Indonesia Stock Exchange (IDX) between 2019 and 2023. The model was chosen using the The Chow, Breusch-Pagan, and Hausman tests, and the findings demonstrated that the pooled ordinary least squares (OLS) model is the most accurate specification. According to the results, neither ESG performance nor PROPER ratings have a big impact on a firm value. Nevertheless, the link between ESG and PROPER is significantly and adversely impacted, demonstrating that the impact of ESG on business value diminishes with increasing levels of verified environmental performance. The model's explanatory capacity is enhanced by including the interaction variable. According to these findings, the alignment of ESG disclosures with actual environmental performance has a greater impact on firm value in Indonesia than either PROPER or ESG alone. In order to ensure that ESG reporting and accredited environmental practices are consistent, businesses are urged to improve the integration of ESG reporting with the PROPER assessment system, while authorities are urged to do the same.